Pengembangan Aplikasi Informasi dan Pencarian Pura berdasarkan Lokasi Terdekat di Kota Malang berbasis Android - I Putu Panji Krisnayasa; Lutfi Fanani; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Malang City besides being famous as a student city is also famous as a tourism city because of its beautiful nature. So do not be surprised if many immigrants settled in the city of Malang. Hinduism as one of the religions in Malang has a population of 0.16% of the population of Malang City. Hinduism has a place of worship which is usually called a temple. In the city of Malang there are five temples which are places of worship for Hindus. The small spread of temples in the city of Malang causes people to find difficulties in finding the closest temple location, especially for migrants. To overcome these problems, the solution offered is to develop an information and temple search application based on the nearest location in Malang based on Android. This application is expected to be able to inform the location of the closest temple, provide the closest route to the temple, and provide information related to the name and telephone number of the temple's organizer, the piodalan day, and the temple worship schedule. In its development, this application was designed using the Object Oriented Design (OOD) approach and implemented with the Object Oriented Programming (OOP) method. Unit testing of three main application methods yields a valid status. The results of validation testing conducted on five test cases produce valid status. The usability test results on five respondents resulted in an SUS 84 score that was included in an excellent scale.